Protective Effects of Pigmentation in Pseudomonas Aeruginosa: Insights on Pyomelanin Production and Inhibition By Ntbc - (:unkn) unknown (My University, 2016)
Pyomelanin is an extracellular, reddish-brown pigment produced by several environmental and pathogenic bacteria and fungi. It is derived from the phenylalanine/tyrosine catabolism pathway and is produced when homogentisate (HGA) is secreted from the cell, auto-oxidized, and self-polymerized. Point mutations or chromosomal deletions in hmgA, which encodes homogentisate 1,2-dioxygenase, result in the accumulation of HGA and subsequent pyomelanin production. My work showed that the pyomelanogenic Pseudomonas aeruginosa clinical isolate PA1111 had a chromosomal deletion of hmgA, while a second pyomelanogenic clinical isolate, DKN343, had a loss of function mutation in HmgA. The 4-hydroxyphenylpyruvate dioxygenase (Hpd) inhibiting compound 2-(2-nitro-4-trifluoromethylbenzoyl)-1,3-cyclohexanedione (NTBC) has been proposed as a treatment for microbial infections by pyomelanin producers. NTBC inhibits Hpd by binding irreversibly to the ferrous metal center in the active site of the enzyme, which should prevent HGA formation and subsequent pyomelanin production. NTBC reduced pyomelanin production in a dose dependent manner in both PA1111 and DKN343; DKN343, however, was more resistant to NTBC than PA1111. NTBC resistance studies revealed that the multi-drug efflux pump MexAB-OprM was responsible for the inherent resistance to NTBC observed in DKN343. One of the functions of pyomelanin is resistance to oxidative stress, and treatment of PA1111 with NTBC resulted in increased sensitivity to H2O2 compared to the untreated strain. Additionally, reduction in pyomelanin production with NTBC had no effect on PA1111 aminoglycoside minimum inhibitory concentrations, which demonstrated that NTBC could possibly be used in conjunction with antibiotics. Pyomelanin was involved in persistence of P. aeruginosa in mouse models of infection, so I investigated macrophage-based killing of pyomelanogenic P. aeruginosa. My results showed little difference in bacterial survival during RAW 264.7 infection between pyomelanin producers and non-producers under different test conditions. My work provided some data for the potential development of NTBC as a treatment for pyomelanogenic microbial infections. NTBC shows some promise as a therapeutic agent, but its effectiveness may be limited in organisms with high levels of antimicrobial resistance such as P. aeruginosa. Future studies should focus on the prevalence of NTBC resistance in other pyomelanogenic organisms to determine the future applications of NTBC as an anti-microbial therapy.
Keywords: Microbiology; Ntbc; Oxidative Stress; Pseudomonas Aeruginosa; Pyomelanin; Raw 264.7 Infection